2020
DOI: 10.1080/10401334.2020.1723593
|View full text |Cite
|
Sign up to set email alerts
|

Social Identification with the Medical Profession in the Transition from Student to Practitioner

Abstract: Phenomenon: This study explores professional identity formation during a final year of medical school designed to ease the transition from student to practitioner. Although still part of the undergraduate curriculum, this "transitional year" gives trainees more clinical responsibilities than in earlier rotations. Trainees are no longer regarded as regular clerks but work in a unique position as "semi-physicians," performing similar tasks as a junior resident during extended rotations. Approach: We analyzed tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 39 publications
0
27
0
1
Order By: Relevance
“…Van den Broek et al studied professional identity formation in a vertically integrated curriculum that builds up to a final year deliberately designed to have students experience the responsibilities of a junior doctor (called 'semiphysician') under supervision. The authors found support for the notion that this curricular structure fosters students' social identification with the community of doctors, and generates a genuine team-member sensation [26,27].…”
Section: Vertical Integration and Individual And Social Identity Devementioning
confidence: 81%
“…Van den Broek et al studied professional identity formation in a vertically integrated curriculum that builds up to a final year deliberately designed to have students experience the responsibilities of a junior doctor (called 'semiphysician') under supervision. The authors found support for the notion that this curricular structure fosters students' social identification with the community of doctors, and generates a genuine team-member sensation [26,27].…”
Section: Vertical Integration and Individual And Social Identity Devementioning
confidence: 81%
“…They related how their decision making was guided by their convictions about their role as a doctor in the decision-making process (beliefs). The strength of their convictions and the firmness with which they were expressed suggested to us that these convictions could be part of their professional identity as a doctor [40][41][42]. Residents not only expressed the conviction that they are responsible for providing the best treatment in each patient, they also expressed the positivist view that each patient has a correct diagnosis which needs to be uncovered to allow them to provide patients with the best evidence-based treatment.…”
Section: Discussionmentioning
confidence: 99%
“…During their longitudinal programme, students assumed the role of a physician, 39 , 48 , 49 , 50 , 51 , 52 experiencing ownership of patients. 50 , 51 , 52 , 53 , 54 , 55 Some students even felt they were the primary physician for their patients, 56 , 57 increasing their sense of responsibility for patient care. 40 , 50 Students felt that the responsibilities they bore for independently providing patient care were adequate for their level of training.…”
Section: Resultsmentioning
confidence: 99%